Exploring Mathematical Operations in Everyday Life with the MathCity Finances Game - Guimarães, Sabrina Dias; Sousa, Pedro Moises de (Anais do Workshop de Sistemas de Informação (WSIS), 2024)
This article discusses the development of an educational digital game to support mathematics teaching for 5th and 6th grade elementary school students. Aligned with the guidelines of the National Common Curricular Base (BNCC) and using Unity 3D technology, the game aims to enhance the understanding of basic mathematical operations in a fun and engaging way. Additionally, the game environment supports the teaching-learning process, facilitating the absorption of mathematical concepts. The agile methodology, with a focus on continuous feedback, resulted in a game tested in schools, showing positive acceptance in aiding learning and enriching the discussion on the role of digital games in education.